Answer:
g = (-5/16)e^(-2t) + Ce^(14t)
Step-by-step explanation:
Given f(t) and g(t).
The Wronskian of f(t) and g(t) is given as
W(t) = 5e^(12t)
If f(t) = e^(14t)
We need to find g(t).
First, Wronskian of f and g is the determinant
W(t) = W(f,g) = Det(f, g; f', g')
= fg' - f'g
But f = e^(14t) and W(t) = 5e^(12t)
So
5e^(12t) = e^(14t).g' - 14e^(14t).g
Multiplying through by e^(-14t)
5e^(-2t) = g' - 14g
Now, we have the first order ordinary differential equation
g' - 14g = 5e^(-2t)
Multiply through by the integrating factor
IF = e^(integral of -14dt)
= e^(-14t)
So, we have
e^(-14t)[g' - 14g] = 5e^(-2t)e^(-14t)
d[ge^(-14t)] = 5e^(-16t)
Integrate both sides
ge^(-14t) = (-5/16)e^(-16t) + C
Multiplying through by e^(14t)
g = (-5/16)e^(-2t) + Ce^(14t)
And this is what we want.